Decay estimate of solutions to the coupled chemotaxis–fluid equations in R3. (October 2018) - Tan, Zhong; Zhou, Jianfeng
Abstract: We are concerned with a model arising from biology, which is coupled system of the chemotaxis equations and the viscous incompressible fluid equations through transport and external forcing. We study the large time behavior of solutions near a constant states to the chemotaxis-Navier–Stokes system in R 3 . Appealing to a pure energy method, we first obtain a global existence theorem by assuming that the H 3 norm of the initial data is small, but the higher order derivatives can be arbitrary large. If the initial data belongs to homogeneous Sobolev norms H ̇ − s ( 0 ≤ s < 3 2 ) or homogeneous Besov norms B ̇ 2, ∞ − s ( 0 < s ≤ 3 2 ), we obtain the optimal decay rates of the solutions and its higher order derivatives. As an immediate byproduct, we also obtain the usual L p − L 2 ( 1 ≤ p ≤ 2 ) type of the decay rates without requiring that the L p norm of initial data is small.